A cost and environmental impact analysis of Ground Source Heat Pumps in European climates - Aresti, Lazaros; Christodoulides, Paul; Stassis, Andreas; Makarounas, Christos; Florides, Georgios A. (My University, 2022)
Ground Source Heat Pumps (GSHPs) are used for space heating and cooling. They form a Renewable Energy System (RES), combined with Ground Heat Exchangers (GHEs) to extract or reject heat from/to the ground. GHEs come in various types such as vertical or horizontal. Compared to conventional Air Source Heat Pumps (ASHPs), GSHPs, although having a higher installation cost, exhibit a higher coefficient of performance (COP). The aim of this paper is to address whether it is economically feasible to install a GSHP as an alternative to an ASHP. In addition, as the environmental impact of a system does not lie in a single aspect, e.g., the cost or COP, it is also useful to identify whether a GSHP system is indeed a sufficiently overall greener solution than an ASHP system. To this end, a case study of a residential building with nearly Zero Energy Building (nZEB) characteristics, for certain heating and cooling loads is considered in Mediterranean, Central and Northern Europe climate conditions. Using GLD software, a GSHP system is studied for a typical vertical U-tube GHE configuration to estimate the length of the boreholes and the COP of the systems. Then, an environmental impact analysis is presented for different GSHP systems in comparison to ASHP systems. The systems undergo a Life Cycle Analysis (LCA), with the annual heating and cooling load as functional unit. The openLCA software is used with the ReCiPe method with a mid-point perspective. The Global Warming Potential impact category is studied. Finally, a cost analysis is presented for the GSHP systems in comparison to ASHP systems and the total energy savings is obtained per case. Hence, the cost breakeven point is estimated per case and is used to assess the viability of each system. It turns out that ASHP systems of specifically designed inverter technology ducted series HP can be highly competitive with GSHP systems.
Keywords: Ground Source Heat Pump Systems; GSHP cost analysis; GSHP Environmental impact; Life cycle analysis